Kyle Erickson, The Early Seleukids, their Gods and their Coins. pp. xiv + 189, 46 ills. 2018. London: Routledge. ISBN 978-0-41579-376-6, hardcover £96.00 - Rutter, Keith (Journal of Greek Archaeology, 2020)
This book examines the coinage of rulers of the Seleucid kingdom down to the reign of Antiochus IV, with particular reference to the deployment on coins of images of divinities that were designed to symbolise and support Seleucid authority, which in its turn required the repeated re–creation of Seleucid legitimacy. Crucial questions throughout are: why was a specific coin type chosen? And, why did the coin iconography develop and change along the lines it did? An introductory chapter covers some of the historical background to Seleucid rule, and introduces (some of) the way(s) in which the images on coins can provide insights into the nature of that rule – in particular by the creation of a Seleucid identity and ideology that was based not only on military success, but also on the support of the gods, in particular Zeus and Apollo. A key conclusion is that some of the images can be interpreted in a ‘polyvalent context’ (p. 9), that is, they could have communicated different meanings depending on the different locales and religious traditions in which they were used. From this point of view an important aim of the book is a better understanding of the ways in which the Seleucid kings related to their native populations. Thus, in Chapter 2 the role of the image of the archer god Apollo sitting on the omphalos is assessed in terms of its potential significance in different areas of the empire: Asia Minor, the Syrian tetrapolis, Babylonia, and Iran.